Restorative Justice as a Paradigm Shift in Indonesia’s Criminal Environmental Law Enforcement - Adi Gunawan; Nadir Nadir; Abdul Wahab Syahroni; Gazali Gazali; Nuzulul Qurnain (Jurnal Pembaharuan Hukum, 2025)
Law enforcement against environmental crimes in Indonesia has yet to fully reflect the primary objective of environmental protection as mandated in Article 54 of Law Number 32 of 2009. Court rulings tend to impose imprisonment or fines without directing perpetrators to engage in environmental restoration. This study aims to analyze the orientation and effectiveness of environmental law enforcement in Indonesia and to propose a more relevant and equitable alternative approach, namely Restorative Justice. This approach is considered more capable of achieving substantive justice, as it emphasizes the involvement of offenders in environmental recovery and provides space for affected communities. This study utilizes a normative legal method employing conceptual and statutory approaches. Secondary data were gathered through a literature review, encompassing primary legal sources such as legislation and court rulings, alongside secondary legal sources from scholarly literature and legal journals. The findings indicate that the current law enforcement approach has not been optimal in realizing ecological justice and needs to be reinforced by a new paradigm that is responsive and forward-looking. Therefore, integrating the Restorative Justice approach into Indonesia’s environmental legal system is an urgent step toward establishing a legal system that is not only repressive but also constructive and restorative.